Minimum lesion detectability as a measure of PET system performance - Adler, Stephen; Seidel, Jurgen; Choyke, Peter; Knopp, Michael V.; Binzel, Katherine; Zhang, Jun; Barker, Craig; Conant, Shielah; Maass-Moreno, Roberto (EJNMMI physics, 2017)
Background A phantom in combination with an imaging protocol was developed to measure the limit of small lesion detection on different PET systems. Seven small spheres with inner diameters ranging from 3.95 up to 15.43 mm were imaged in a Jaszczak ECT Phantom, in air, in a cold background, and with sphere to background contrast ratios of 15:1 down to 1.88:1. The imaging times varied from 1 to 16 min. The imaging protocol was performed on the Gemini TF and Vereos by Philips, the mCT and HRRT by Siemens, and the Discovery 710 by General Electric. For each scanning condition, the images were reconstructed with image voxel sizes of 1 to 4 mm cubic voxels. The reconstruction method used for each system was the one recommended by the manufacture to achieve best small image lesion detection results. A human observer study was performed to determine the smallest observable sphere for each scanning condition. Results All systems were able to image the smallest sphere of 3.95 mm inner diameter at the 15 to 1 signal to background ratio when imaged for 16 min. For a typical whole body per bed position scan time of 2 to 4 min, the smallest imaged sphere varied between 4.95 and 6.23 mm at the 15:1 contrast ratio and 12.43 and 15.43 mm at a contrast ratio of 1.88:1. In general, all systems were consistent with the Rose criteria when determining lesion detectability. Conclusions Besides demonstrating that the current state of the art clinical PET/CT systems have the same lesion detection ability, the study demonstrates how sensitive scan time can be to detecting small lesions which have a relatively small contrast uptake in the range of just 2:1. This should help guide imaging protocols to use longer scan times over regions of the subject in which small lesions are suspect.